Emphysematous Pyelonephritis in Renal Allograft - a case report - Alhajjaj, Fahad Saleh; Pasha, Farooq (International Journal of Health Sciences, 2016)
Emphysematous pyelonephritis (EPN) is a rare disease with devastating outcomes in healthy adults. It may affect renal allografts resulting in higher mortality rate, graft loss and permanent dialysis. Presentation is highly variable and non-specific requiring higher degree of suspension. Optimal management of EPN is controversial with recent case reports challenging a previously suggested management pathway. We report a case of a 71-year-old man who presented in septic shock who was diagnosed with EPN in an allograft kidney in the emergency department, treated with antibiotics and medical support but died on the 6th day of presentation. Based on the scarce literature of EPN in allograft kidneys, a nephrectomy might be indicated in a similar patient presentation.